Health knowledge and livelihood experiences with COVID-19 amongst Arizona residents - Fingesi, Tina; Chung Yon, Lin; Soto, Sheila; Rosales, Cecilia (Frontiers in Public Health, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic is an ongoing public health concern that is rapidly evolving and has impacted individuals and communities differently. We analyzed a questionnaire-based publicly available and deidentified dataset to evaluate the perceptions, experiences, and impacts of COVID-19 among Arizona residents. The survey included 1472 eligible Spanish-speaking participants in Southern (Pima, Santa Cruz, Cochise, Yuma County) and Central Arizona (Maricopa County). Eighteen questions which included participants’ health and socio-economic status, source of information on COVID-19, preventive measures, the impact of COVID-19 on household income, and vaccination status were administered to the survey respondents. The data was analyzed using RStudio; there was an unequal proportion of the reported sources of COVID-19 information between Southern and Central Arizona participants. Of the 461 (31.3%) participants in Maricopa County, the majority reported television (56%) and social media (20%) as their primary source of information. Whereas of the 1011 (68.7%) participants in Southern Arizona, the majority reported social media (37%) and television (32%) as the major source of information on CODID-19. Overall, 82% of the participants were vaccinated, with a statistically significant difference between the proportion of vaccinated individuals in the Southern and Central Arizona (chi-square p-value of 0.00139). More individuals in Southern Arizona (68.7%) participated in the survey than in Central Arizona (31.3%) across both genders; with 58% of women reporting loss of jobs due to COVID-19. This study demonstrated that the COVID-19 pandemic profoundly had a more socio-economic impact on women than men, particularly Hispanic women in this subset.